Investigating emotion in Malay, Australian and Iranian individuals with and without depression - Jobson, Laura; Mirabolfathi, Vida; Moshirpanahi, Shiva; Parhoon, Hadi; Gillard, Julia; Mamat @ Mukhtar, Firdaus; Moradi, Ali Reza; Mohan, Sindhu (Nature Publishing Group, 2019)
This study investigated the influence of culture and depression on (1) emotion priming reactions, (2) the recall of subjective experience of emotion, and (3) emotion meaning. Members of individualistic culture (Australia, n = 42) and collectivistic culture (Iran, n = 32, Malaysia, n = 74) with and without depression completed a biological motion task, subjective experience questionnaire and emotion meaning questionnaire. Those with depression, regardless of cultural group, provided significantly fewer correct responses on the biological motion task than the control group. Second, the collectivistic control groups reported greater social engaging emotion than the Australian control group. However, the three depressed groups did not differ culturally. The Australian depressed group reported significantly greater interpersonally engaging emotion than the Australian control group. Third, the collectivistic groups reported significantly greater social worth, belief changes and sharing of emotion than the individualistic group. Depression did not influence these cultural effects. Instead we found that those with depression, when compared to controls, considered emotions as subjective phenomena, that were qualifying for relationships with others, and associated with greater agency appraisals. The applicability of the biocultural framework of emotion in depression was considered.